The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1200/jco.1992.10.11.1690
|View full text |Cite
|
Sign up to set email alerts
|

Autologous versus allogeneic bone marrow transplantation for non-Hodgkin's lymphoma: a case-controlled analysis of the European Bone Marrow Transplant Group Registry data.

Abstract: This study suggests that ABMT and alloBMT for non-Hodgkin's lymphoma are comparable, with the exception of lymphoblastic lymphoma in which a graft-versus-lymphoma effect may account for the lower relapse rate for patients who underwent alloBMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(93 citation statements)
references
References 10 publications
6
85
1
1
Order By: Relevance
“…A case controlled analysis of allogeneic vs autologous transplantation in 101 patients using data from the EBMTR was conducted and revealed a somewhat lower risk of relapse after allogeneic transplantation compared to auto-BMT (23 vs 38%). 8 However, again, disease-free survival was similar (49 vs 46%) due to higher toxicity in the allo-transplant group. In this study, a correlation between the development of chronic GVHD and protection from relapse was identified, supporting the notion of a graft-versus-lymphoma effect.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A case controlled analysis of allogeneic vs autologous transplantation in 101 patients using data from the EBMTR was conducted and revealed a somewhat lower risk of relapse after allogeneic transplantation compared to auto-BMT (23 vs 38%). 8 However, again, disease-free survival was similar (49 vs 46%) due to higher toxicity in the allo-transplant group. In this study, a correlation between the development of chronic GVHD and protection from relapse was identified, supporting the notion of a graft-versus-lymphoma effect.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies in patients with NHL have reported lower relapse rates after allogeneic BMT than after autologous transplant. [5][6][7][8][9] Lastly, in recent years, the risk of long-term complications such as myelodysplasia and secondary leukemias following autologous BMT for lymphoma has been recognized with increasing frequency. 10,11 If the morbidity and mortality associated with allogeneic transplantation could be reduced, then it might prove a superior alternative to autologous transplant procedures in certain patients with recurrent lymphoma.…”
mentioning
confidence: 99%
“…Most retrospective studies on this issue showed that patients treated with allogeneic SCT were usually affected by more advanced or refractory disease, thus suggesting the existence of immune-mediated anti-tumor activity. [6][7][8] The additional evidence of clinical and molecular responses after the withdrawal of immunosuppressive therapy or donor lymphocyte infusions further supported the idea of an underlying GVL effect. 9,10 However, the main obstacle to a wide application of myeloablative allogeneic SCT, as a salvage strategy, was the high incidence of transplantrelated mortality (TRM) that offset the benefit of the GVL effect in terms of overall survival.…”
mentioning
confidence: 99%
“…The median time to reach more than 0.5 × 10 9 /l ANC was 16 (range, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] …”
Section: Engraftmentmentioning
confidence: 99%
“…Non-randomized studies demonstrated a reduction of relapse by approximately half compared to autologous transplantation, but this advantage was upset by the high treatment-related mortality. [12][13][14][15] Nevertheless, some patients with poor prognosis NHL attain long-term clinical remissions. [16][17][18][19][20] As other hematologic malignances NHLs are characterized by non-random genetic alterations.…”
Section: Introductionmentioning
confidence: 99%